The Application of “Internet+” in the Ageing Adaptation of Elderly People with Disabilities at Home - Huang Juan; Li Li; Mai Jiasong; Zhang Lifang; Huang Baoying (Journal of Mathematics)
This paper focuses on the role of the Internet in empowering social work to intervene in ageing-in-place services for the disabled elderly in terms of time, space, and resources. Through the practical analysis of home care service providers, the advantages and characteristics of the “Internet” for ageing-in-place services for the disabled elderly are identified, as well as some of the problems that exist in the current intelligent home care service platform. This paper proposes to improve and optimize the “Internet+” by fully enhancing the technical empowerment of the Internet, improving the integration and spanning of space, and giving full play to the role of social work on the Internet. This paper proposes to improve and optimize the “Internet+” elderly home care services for the disabled, so as to solve to a certain extent the practical problems faced by the “Internet+” elderly home care services in the early stage of development. The significance of this paper is that, through the study of the “Internet+” home care services for the elderly with disabilities, the process of the services is sorted out and summarized, and suggestions and measures are put forward for its shortcomings, providing practical methods and feasible paths for future generations, which are of great significance for other social work agencies using Internet tools.